POLA KOMUNIKASI INTERPERSONAL MAHASISWA YANG BERORIENTASI SEKSUAL GAY - Putra, Reza Ardiansyah; Sumarah, Noorshanti; Satvikadewi, AAI. Prihandari (representamen, 2016)
This research entitled patterns of Interpersonal Communications Students with Gay sexualorientation (a case study of Interpersonal Communication in daily interactions of Gay Students). Thepurpose of this research is to know the symbols (Non Verbal Communication) and to know the symbollanguage (Verbal communication) used in the gay student interact with her environment(homosexuals and Heterosexuals) as well as how communication affects the gay student identificationin social environment in berinterak. that verbal and non verbal communication students in her socialenvironment is not gay so real in the world of hetroseksual. Gay covered many of which straddledifferent from gay open is more conspicuous, even so homosexuals could identify one another fromthe gaze of the eyes, body language, looks, and fragrances are used in excess, as well as languageand speech they use, but communication also happens to homosexuals in the virtual world bydemonstrating the full form of interaction and language use homosexual in shows themselves freelyon social media. In his intercourse the formation of gay student identification of its communication isthe creation of new languages to keep eksistentsinya and although most shut down, homosexuals havealways had a natural trait with hand gestures that are curved, and talk with supple lip movements thatare a little bit like a woman.Key words: Interpersonal Communication Patterns, Gay Students in daily interactions.